GAYA BAHASA PERTENTANGAN PADA NOVEL GARIS WAKTU KARYA FIERSA BESARI - Mifta Sari Wardani; Wiwik Surya Utami (Universitas Batanghari, 2025)
This research aims to analyze the use of contrastive stylistic devices in the novel Garis Waktu by Fiersa Besari, focusing on the identification and frequency of various stylistic devices and explaining the most dominant one. Using Henry Guntur Tarigan's theory of stylistic devices, this research categorizes the contrastive stylistic devices in the. The research method used is descriptive qualitative with a text analysis approach. Data is taken from quotes in the novel which are then classified according to Tarigan's theory of stylistic devices. The results show that contrastive stylistic devices are the most dominantly used in the novel Garis Waktu. This style creates a strong dramatic and emotional effect, enriching the narrative and deepening the characterization of the characters. The strength of using these stylistic devices lies in their ability to evoke readers' emotions and reinforce the message the author wants to convey. This novel not only presents a complex love story but also provides life lessons about sincerity and acceptance.